Analysis of Water-Saving Irrigation with Organic Materials at Different Percentages for Rice Cultivation - Dhinar Yoga Hanggung Legowo; Fatchan Nurrochmad; Endita Prima Ari Pratiwi (Journal of the Civil Engineering Forum, 2020)
Gemolong subdistrict in Sragen Regency of Central Java, Indonesia has a rainfed rice area of 2,047.64 hectares. Water is very limited during the dry season and this usually makes farmers use costly groundwater pumps for irrigation. This means conventional method involving the continuously flooded irrigation combined with chemical fertilizers which are considered water-wasteful and hazardous to the soil is the current practice in the area. However, water saving-irrigation with the addition of organic material has been discovered to be an alternative solution to this problem. Therefore, this study aimed to determine the effect of this method on water productivity using four variations of water-saving irrigation treatment and composition of organic application as well as one control treatment involving conventional method with chemical fertilizers. Meanwhile, composted rice straw was used as organic material and applied at 20% and 40% composition. The results showed the application of organic material boosted rice production while the water-saving method increased water productivity. Applying rice straw to the soil at 20% and 40% was discovered to have increased water productivity by 15% and 19% compared to the control treatment. Moreover, the application of 20% rice straw to water-saving irrigation method saved up to 19% water and increase its productivity by 16.5% in comparison with the control treatment. However, 40% under water-saving irrigation method reduced the water productivity by 2% even though it saved up to 27% water needed for irrigation. It is, therefore, recommended that water-saving methods added with 20% organic material be implemented as alternative rice cultivation procedures during dry season and period of water scarcity.